Psychosocial work environment in Swedish primary healthcare: a cross-sectional survey of physicians' job satisfaction, turnover intention, social support, leadership climate and change fatigue - Hanna Fernemark; Nadine Karlsson; Janna Skagerström; Ida Seing; Elin Karlsson; Emma Brulin; Per Nilsen (BMC, 2024)
Abstract Background Primary healthcare, the first line of care in many countries, treats patients with diverse health problems. High workload, time pressure, poor job control and negative interpersonal experiences with supervisors have been documented in primary healthcare. The work environment in primary healthcare is also affected by several types of changes. Aim We aimed to explore the levels of job satisfaction, turnover intention, social support, leadership climate and change fatigue according to physicians in Swedish primary healthcare. We also aimed to identify and characterize physicians exhibiting both high turnover intention and low job satisfaction, i.e., "discontent with current job". Methods A cross-sectional survey based on a random sample of physicians working in Swedish primary healthcare. Results Approximately one-quarter of the respondents were discontented with their current job. Discontent was negatively associated with poor general health and change fatigue among the respondents; social support from colleagues and a favorable leadership climate showed positive associations in terms of reducing the levels of discontent with current job. Conclusions The findings of this study highlight the association between low levels of job satisfaction and high levels of turnover intention (i.e., discontent with current job) among physicians in primary healthcare. Moreover, these variables exhibited a strong association with physicians' general health; poor health significantly increased the likelihood of discontent with current job. Our findings also show that experiencing change fatigue is associated with discontent with current job among physicians in primary healthcare. This knowledge can help identify and improve shortcomings within the psychosocial work environment in Swedish primary healthcare.